Interventions to Reduce the Overuse of Imaging for Pulmonary Embolism: A Systematic Review. Issue 1 (1st January 2018) - Deblois, Simon; Chartrand‐Lefebvre, Carl; Toporowicz, Kevin; Chen, Zhongyi; Lepanto, Luigi
Abstract : BACKGROUND: Imaging use in the diagnostic workup of pulmonary embolism (PE) has increased markedly in the last 2 decades. Low PE prevalence and diagnostic yields suggest a significant problem of overuse. PURPOSE: The purpose of this systematic review is to summarize the evidence associated with the interventions aimed at reducing the overuse of imaging in the diagnostic workup of PE in the emergency department and hospital wards. DATA SOURCES: PubMed, MEDLINE, Embase, and EBM Reviews from 1998 to March 28, 2017. STUDY SELECTION: Experimental and observational studies were included. The types of interventions, their efficacy and safety, the impact on healthcare costs, the facilitators, and barriers to their implementation were assessed. DATA SYNTHESIS: Seventeen studies were included assessing clinical decision support (CDS), educational interventions, performance and feedback reports (PFRs), and institutional policy. CDS impact was most comprehensively documented. It was associated with a reduction in imaging use, ranging from 8.3% to 25.4%, and an increase in diagnostic yield, ranging from 3.4% to 4.4%. The combined implementation of a CDS and PFR resulted in a modest but significant increase in the adherence to guidelines. Few studies appraised the safety of interventions. There was a lack of evidence concerning economic aspects, facilitators, and barriers. CONCLUSIONS: A combined implementation of an electronic CDS and PFRs is more effective than purely educational or policy interventions, although evidence is limited. Future studies of high‐methodological quality would strengthen the evidence concerning their efficacy, safety, facilitators, and barriers.